EXAMINATION OF THE RELATIONSHIP BETWEEN ATTACHMENT STYLES AND SPOUSE PREFERENCES - Rizvance Masan, Sehida; Bolcal, Derya (International Scientific Journal Vision, 2024)
According to attachment theory, once an attachment style is determined as secure or insecure in early childhood, it shows little variation later in life. In this process, secure attachment is stated as a healthy communication. Insecure attachment style has been associated as a determinant of psychopathology in later life. Anxious/ambivalent attachment, which is one of the insecure attachment styles, has been associated with anxiety disorders. It has also been associated with avoidant attachment behaviour disorder, which is a form of insecure attachment, and other expressive pathologies. Between secure attachment and Romanticism and Spouse Attitude, between living together, idealization and full trust, significant positive, avoidant attachment and Romanticism and Spouse Selection Attitude, living together, love is sufficient, effort, idealization and opposite poles between meaningfully positive, anxious attachment and idealization A significant positive correlation was found between and opposite poles.